Diagnostic Accuracy of Serum Matrix Metalloproteinase‐7 for Biliary Atresia. Issue 6 (15th November 2018) - Yang, Li; Zhou, Ying; Xu, Pei‐pei; Mourya, Reena; Lei, Hai‐yan; Cao, Guo‐qing; Xiong, Xiao‐li; Xu, Hui; Duan, Xu‐fei; Wang, Na; Fei, Lin; Chang, Xiao‐pan; et al.
Abstract : The diagnosis of biliary atresia (BA) remains a clinical challenge because affected infants have signs, symptoms, and serum liver biochemistry that are also seen in those with other causes of neonatal cholestasis (non‐BA). However, an early diagnosis and prompt surgical treatment are required to improve clinical outcome. Recently, the relative abundance of serum matrix metalloproteinase‐7 (MMP‐7) was suggested to have discriminatory features for infants with BA. To test the hypothesis that elevated serum concentration of MMP‐7 is highly diagnostic for BA, we determined the normal serum concentration of MMP‐7 in healthy control infants, and then in 135 consecutive infants being evaluated for cholestasis. The median concentration for MMP‐7 was 2.86 ng/mL (interquartile range, IQR: 1.32‐5.32) in normal controls, 11.47 ng/mL (IQR: 8.54‐24.55) for non‐BA, and 121.1 ng/mL (IQR: 85.42‐224.4) for BA ( P < 0.0001). The area under the curve of MMP‐7 for the diagnosis of BA was 0.9900 with a cutoff value of 52.85 ng/mL; the diagnostic sensitivity and specificity were 98.67% and 95.00%, respectively, with a negative predictive value of 98.28%. Conclusion: Serum MMP‐7 assay has high sensitivity and specificity to differentiate BA from other neonatal cholestasis, and may be a reliable biomarker for BA.